ANALISIS PENERAPAN AKUNTANSI BIAYA PADA PENENTUAN HARGA JUAL KAMAR HOTEL DI HOTEL SANTIKA BENGKULU - dewi aprida (Universitas Prof.Hazairin,SH Bengkulu, 2025)
The purpose of this research to analyze the implementation of cost accounting in determining hotel room selling prices At Hotel Santika Bengkulu in January-June 2025. This research method uses descriptive approach. The respondents in this study consisted of financial manager and management with a case study design, where data was collected through literature reviews, field observations, in-depth interviews with management, and analysis of the hotel’s financial reports. The findings reveal that Hotel Santika Bengkulu applies the full costing method to identify all operational cost components, including fixed costs (building rent, asset depreciation), variable costs (electricity, water, cleaning services), and semi-variable costs (employee salaries, facility maintenance). Based on cost calculations, the room selling price is determined using a cost-plus pricing strategy, adding a 25% markup to the total cost per room. Further analysis shows that the largest cost component comes from semi-variable costs (41%), followed by fixed costs (37%) and variable costs (22%). Using this approach, the standard room price is set at IDR 699,000 per night, which is deemed competitive in the local Bengkulu market while covering operational costs and generating optimal profit. This study concludes that the systematic application of cost accounting not only improves pricing accuracy but also supports strategic management decision-making in optimizing resources.